Gender differences in behavioral and psychological crisis responses: a cross-national Oaxaca-Blinder analysis - Jiajia Li; Jie Fan; Jun Li; Abbas Ali Chandio (Humanities & Social Sciences Communications)
Abstract Gender disparities in behavioral and psychological responses to public crises have become increasingly significant, particularly in the aftermath of such events, due to their far-reaching socio-economic consequences. This study investigates these disparities using data from a cross-national survey of over 6,000 individuals across six countries. Employing the Oaxaca-Blinder decomposition technique, the study quantifies both the explained and unexplained components of gender differences in coping behaviors, travel intentions, and negative emotions stemming from the COVID-19 pandemic. Notably, we explore a novel channel by examining the moderating role of individualism, as measured by Hofstede’s cultural index, in shaping gender differences in these crisis responses. Our findings reveal that women are more likely to engage in preventive behaviors and experience higher levels of negative emotions compared to men. Meanwhile, men’s work-related travel intentions are more affected by the pandemic, whereas women’s leisure-related travel intentions are more impacted. Furthermore, women from individualistic cultures are less inclined to adopt preventive behaviors. In addition, different income groups and countries display heterogeneous gender dynamics in these crisis responses. Grounded in the Activating Event-Belief-Consequence (ABC) theory, our results highlight the necessity of adopting a gender-sensitive approach in policy-making and public health interventions, especially for women in economically disadvantaged and collectivist societies, thereby fostering equitable and effective outcomes in the face of future public crises across different regions and cultures.